Evaluation of Knowledge, Attitude and Practices of Parents toward their Children Oral Health Compared with their Dental Caries status - Dikshit, Parajeeta; Limbu, Senchhema; Gupta, Sujaya; Pradhan, Ruby (Birat Journal of Health Sciences, 2018)
Introduction: Oral health is an integral component of overall health and well-being. Unfavorable oral hygiene habits cause early development of dental caries. Parents play a vital role in the oral health habits of their children. The oral care for the children can be improved by enhancing the oral health knowledge of their parents. Objectives: The objective of this study was to find out the knowledge, attitude and practices of parents toward their children oral health compared with dental caries status. Methodology: The sample consisting of 168 parent-child pair attending the Pedodontics department from November-December 2017 participated in the study after approval from Institutional review committee. A validated Nepali version of a structured questionnaire was used to collect the information on the knowledge, attitude and practice of the parents about oral health which was compared with the dental caries status of children and parents. The caries status was evaluated using the WHO criteria. The data was tabulated and subjected for statistical analysis. Results: Most of the parents (89.3 %) were aware that dental caries was the most common dental disease affecting children. Around 57.7% knew the importance of fluoride in prevention of dental caries. The children had higher dental caries rate than parents which was statistically significant. The overall oral health knowledge and attitude of the parents was adequate but their practice was inadequate. Inadequate attitude and practice of the parents had statistically significant impact on the caries status of the child. Conclusions: The parent's oral hygiene knowledge has an effect on their children oral health. So adequate education for parents is necessary to improve the influence of their dental health habits on their children's oral health. BJHS 2018;3(2)6: 447-452.